THE PARENT ROLE IN EARLY CHILDHOOD CHARACTER BUILDING - Dwi Hayantina Sunarni (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Having children who has a good character is every parent wish. For having this good character its need to be done from early age. All the parents has an important role on building this character to their children. Children as a good imitators will do what they see, so that the parent in this case need to be a good role model to the children. Like a wise words say an apple never fall far from the tree, so its mean childrens is the reflection of their childrens. If we want to have children with good character so the parent must have a good character too. So that the parent has a main role to building this early age children. Every child is like a clean white paper, they will follow every direction that been given to them. Not only the parents, school and the environtment having a huge role to building this children character. But back again if the parents already put the values of the good character the children wont absorb other influence from their environment. So it means that father and mother roles in the family becoming the most important things on this children character building. Other than that the parent responsibilities to their children character building need to be their main concern.